A Modal Criterion for Epistemic Argumentation - de Grefte, Job (Informal Logic, 2022)
In this paper, I spell out and argue for a new epistemic theory of argumentation. Contrary to extant views, this theory is compatible with a pluralistic framework on argumentation, where the norms governing argumentation depend on the aim with which we engage in the practice. A domain of specifically epistemic argumentation is singled out, and I argue based on recent findings in modal epistemology that this domain is governed by the modal norm of safety; where a belief is safe just in case it is produced by a method that would not easily produce a false belief. While this criterion is well-known and uncontroversial in epistemology, it has hitherto not been applied to epistemic theories of argumentation. I show that the norm allows for a novel and superior perspective of the relevance of the persistent interlocutor in argumentation theory, and on the relation between dialectical and epistemic norms more generally.